EFFECTIVE IN SILICO SCREENING OF NATURAL AND SYNTHETIC COMPOUNDS FOR INHIBITION OF P-38 MAPK AS A THERAPEUTIC APPROACH IN PROGRESSIVE END-STAGE RENAL FAILURE - RAMESH KUMAR G; AVINASH RAMANI; MANONANTHINI THANGAM (International Journal of Pharma and Bio Sciences, 2015)
Apoptosis and Epithelial to Mesenchymal Trans-differentiation (EMT) are considered to be the primary cellular pathophysiological mechanism that are mediated by response-specific p-38 signaling networks in various forms of inflammatory fibrogenic diseases. Growth factors such as Transforming Growth Factor-b (TGF – b),Mitogen Activated Protein Kinases (MAPKs) including p-38 MAPK and others are important for the signal transduction of response-specific signaling networks in various forms of renal tissue injury leading to fibrosis. p-38 MAPK is an important target for the complex pro-inflammatory cytokine pathway and play a major role in the pathophysiology of various diseases like cancers, liver cirrhosis, renal failure, or cystic fibrosis. Over-expression of p-38 MAPK can induce renal fibrosis, causing kidney tubule damage, and ultimately End-Stage Renal Disease (ESRD). It has been recently found that, using various types of antagonists against these kinases, one can halt or even reverse renal fibrosis and even partially cure renal failure. Thus, targeting p-38 MAPK will play a major role in the novel targeted drug development for the prevention of complete damage of the kidney. Structurally diverse natural anti-inflammatory compounds such as flavones, indoles and stilbenes and their semi-synthetic derivatives were screened for the evaluation of inhibitory potential of p-38 MAPK by Virtual High Throughput Screening (vHTS). The p-38 MAPK protein was remodeled and the compounds were docked using an efficient docking algorithm to find out the good inhibitor with better pharmacological action. Quantitative Structural Activity Relationship (QSAR) studies were performed for the evaluation of molecular descriptors for the prediction of drug likeliness and druggability properties. It helped in the identification of potential leads that could be used as an antagonist for p-38 MAPK.